Penerapan Insentif pada Toko Retail : (Studi Kasus Agen Sembako Bu Ira Di Krian, Sidoarjo) - Lutfika Arifa Faizati; Intan Pandini; Hwihanus Hwihanus (FEB Universitas Maritim Semarang, 2024)
This research explores the impact of implementing incentives at the Bu Ira basic food agency in Krian, Sidoarjo on employee performance, with a focus on sales bonuses and non-financial incentives. The research results show that sales bonuses related to target achievement provide additional motivation for employees to increase sales, especially when bonuses are linked to certain products that have higher profits. Additionally, non-financial incentives such as recognition for good performance have proven effective in building team spirit and increasing job satisfaction. The discussion involved understanding that incentive design must be tailored to the grocery store context, taking into account the unique characteristics of this industry. Sales bonuses, when tied to specific types of products, can provide a greater motivational boost for employees. Recognition of good performance can be realized in the form of promotion or additional training, providing added value in employee career development. Flexibility in incentive design, effective communication, and continuous evaluation of the effectiveness of incentive programs are the keys to success. The results of this research provide insight for business owners and managers in the grocery agency industry to design incentive programs that suit employee needs and business goals, as well as accommodate changes in the industrial environment.